Students’ perception of digital media for English teaching learning - Edi Sunjayanto Masykuri; Basuki Basuki (Universitas Ahmad Dahlan, 2022)
This research was to find out the students’ perception towards digital media for ELT in Purworejo Muhammadiyah University. This research generally answered the question: how is students’ perception towards digital media for ELT in Purworejo Muhammadiyah University. The researchers collected the data through a questionnaire. There were twenty-seven of fourth semester students at Purworejo Muhammadiyah University participated in this research. This research used case-study design. Descriptive analysis was used to analyze the data from questionnaire. The result of this research showed that the students had high perception on digital media as an English reading material. The mean score of the questionnaire was 3.55 which can be interpret in the “High” category. Besides there were some difficulties faced by students and teacher in using digital media, such as limited mobile phone facilities, limited internet packages, and poor signal problems.